Popular theory [videorecording (DVD)] - Scher, Ali; Swanson, Joe (Screenwriter); Reid-Gantzert, Sophia; Lambert, Lincoln; Jackson, Marc Evan, 1970-; East, Chloe; Ponzio, Melissa, 1972-; Bondurant, Eugenie, 1961-; Sterling, Kat Conner; Hines, Cheryl (Breaking Glass Pictures, 2024)
Twelve-year-old Erwin is a genius, far smarter than any of her high school classmates. But Erwin's genius has come at a price, isolation. She doesn't have any friends and even her sister thinks she's a social leper. Determined to win the State Science Fair, she teams up with classmate Winston, a fellow outcast and chemistry guru, to create a popularity chemical which they add into sticks of chewing gum.